Pengaruh Shopping Lifestyle, Fashion Involvement Dan Hedonic Shopping Motivation Terhadap Impluse Buying Pada Produk Merk Converse (Studi Kasus Pada Mahasiswa Malang) - Safitri, Melfarya; Farida, Eka; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This investigate was conducted to decide and analyze the impact of shopping way of life, design association and hedonic shopping inspiration on drive buying of Speak brand items. The populace within the inquire about is understudies who utilize Converse products in Malang, the precise number of which is obscure. The approach strategy employments a non-probability sampling method, specifically purposive testing, which could be a test collection strategy based on certain criteria employing a survey disseminated to 95 respondents and utilizing the SPSS investigation instrument. The inquire about comes about appear that shopping way of life, design association and hedonic shopping inspiration at the same time impact the motivation buying variable and somewhat shopping way of life, design association and hedonic shopping inspiration impact the motivation buying variable. Keywords: Shopping Lifestyle, Fashion Involvement, Hedonic Shopping Motivation, Impulse Buying.